2004
DOI: 10.2355/isijinternational.44.59
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Parameters on the Swelling Behaviour of Cement-bonded Briquettes

Abstract: The use of cement-bonded agglomerates of iron-rich by-products generated in iron and steel plants as burden material for blast furnaces is becoming quite common. It has been observed that under certain conditions the briquettes containing pellet-fines show a tendency to swell catastrophically when reduced at 900-1 000°C using carbon monoxide as a reducing agent. This swelling is dependent upon a number of processing parameters, such as: composition of briquettes, particle size of raw material, amount of cement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 1 publication
(1 reference statement)
0
30
0
Order By: Relevance
“…[23][24][25] The reduction rate is fast when H2 is present in the reducing gas, and metal bond resists against swelling.…”
Section: Reduction Of Iron Oxide With Hydrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] The reduction rate is fast when H2 is present in the reducing gas, and metal bond resists against swelling.…”
Section: Reduction Of Iron Oxide With Hydrogenmentioning
confidence: 99%
“…Singh and Bjorkman [23][24][25] studied the effect of reduction conditions on the swelling behavior of cement-bonded briquettes. It was observed that, under certain conditions, the briquettes containing fines generated from pellets during handling show a tendency to swell catastrophically when reduced at 900-1 000°C using CO.…”
Section: Introductionmentioning
confidence: 99%
“…Coke is used as the primary reducing agent in two blast furnaces. Coke oven gas, composed mainly of H 2 , CH 4 and CO with heating value of 16-18 MJ/Nm 3 , is utilized chiefly in the steel plant processes. Sulfur and benzene are sold as by-products to other industries.…”
Section: System Boundariesmentioning
confidence: 99%
“…Sintering, which is a unit process to agglomerate iron ore fines in high temperature, has been traditionally used to refine many of the solid residues produced inside the system boundaries [2,3]. In steel plants that do not include a sintering plant, solid iron-bearing residues can be recycled back to the blast furnace via a briquetting plant where cement-bonded briquettes are produced [4]. Another option for treating dust and scales is to use alternative recycling technologies, e.g., Oxycup or rotary hearth furnace (RHF) [5].…”
Section: Introductionmentioning
confidence: 99%
“…4) Maneesh et al 5,6) studied the effect of reduction conditions on the swelling behavior of cement bonded briquettes. They found that the swelling of briquettes increases with the increase in average particle size of the raw material also the briquettes containing a larger amount of slag-forming oxides, CaO, SiO 2 , MgO and Al 2 O 3 may swell more.…”
Section: Introductionmentioning
confidence: 99%